Avaliação da relação entre evidenciação das práticas ambientais e sociais no desempenho financeiro de empresas do setor bancário - Melo, Guilherme Erick de Albuquerque (2019)
The implications resulting from the interaction of companies with the elements that make up their internal and external panorama are not yet fully understood. However, the descriptive studies of the real impacts caused by these institutions - especially with regard to environmental and social issues - have been growing in recent years. The financial sector, more specifically the banking sector, as an actor in the theater of the political and economic transformations of a country, is also covered by the questioning of society about the role of companies within it. The objective of this study was to investigate the relationship between the act of bringing to public knowledge the environmental and socially responsible actions by a predetermined list of institutions in this field and the behavior of their respective financial performance. The path chosen to obtain the information processed in the study was the access to the annual reports of these organizations, mainly through the Global Report Initiative (GRI) database. From the reading of the information contained therein, using the application of a binary metric and the Pearson Coefficient in the analysis of such data, it was reached the subsequent results. In the end, the existence of a clear link between the variables was not concluded. Reflecting few correlations of significance; there is no such comprehensive range that would point to confirmation of the association between the above factors.